Pengaruh Parental Favoritism terhadap Sibling Rivalry pada Usia Dewasa - Rahmawati Mahardhika Hariaji; Assyifa Salsabila; Rini Sugiarti; Fendy Suhariadi (Psychopolytan : Jurnal Psikologi, 2025)
This study aims to determine the effect of parental favoritism on sibling rivalry in adulthood. Sibling relationships are often characterized by a love-hate relationship, where individuals value their siblings as people who support them lovingly, but also as aggressive and antagonistic people. Sibling rivalry is influenced by many factors, one of which is parental favoritism. A quantitative approach was used in this study with parental favoritism scale and sibling rivalry scale for data collection. Furthermore, the data were analyzed using simple linear regression test. The findings of the analysis show that there is a positive influence of parental favoritism on sibling rivalry with a regression coefficient of 0.720 and a p value <0.001. The result of the percentage of the influence of parental favoritism on sibling rivalry is 86.5% (R square = 0.865), while the other 13.5% is due to other factors outside the study. Therefore, it is concluded that the research hypothesis is accepted, and it means that parental favoritism affects sibling rivalry in adulthood. Thus, the importance of parental awareness in treating children fairly in order to minimize the potential for sibling rivalry that can continue into adulthood.